The Frequency of Human Polyomavirus BK in Patients with Systemic Lupus Erythematosus: A Cross-Sectional Case-Control Study - Behzadi Sheikhrobat , Sheida; Kaydani , Gholam Abbas; Makvandi, Manoochehr; Rajaee, Elham; Ahmadi Angali , Kambiz (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Systemic lupus erythematosus (SLE) is an autoimmune disease and human polyomavirus BK (BKV) can be reactivated in patients with SLE due to the changes in the immune system and use of immunosuppressive drugs. In this study, we evaluated the prevalence of BKV infection among patients with SLE referred to Golestan hospital in Ahvaz, Iran between April 2013 to June 2016. Methods: In this cross-sectional study we studied 75 individuals including 40 patients with SLE and 35 normal individuals. Urine and blood samples were taken and DNA was extracted from urine and plasma. Polymerase Chain Reaction (PCR) test was used to detect the BKV genome and positive samples were sequenced to confirm BKV. BioEdit software and MEGA 6.0 software were used for phylogenetic analysis to assemble the viral genome. A phylogenetic tree was constructed by neighbor-joining analysis with 1,000 replicates of the bootstrap resampling test using Mega 6.0. Statistical analysis was done by SPSS version 22. Results: Among the 40 patients, 2 (5%) were men and 38 (95%) were women. The mean age of the patients was 39±10 years. 2.5% of plasma from patients with SLE were positive for BKV but none of the controls were positive in this regard.0% of control groups (p=0.346). Whereas in urine samples, 17.5% and 11.4% (p=0.458) of patients and the control group, were positive for BKV, respectively. However, there was no statistically significant difference between the patients and controls. Conclusion: BKV reactivation occurs in 17.5% of patients with SLE during immunosuppression therapy. Therefore, more studies on BKV DNA by highly sensitive molecular assays in Patients with SLE seem to be necessary. *Corresponding Author: Gholam Abbas Kaydani; Email: kaydani-ga@ajums.ac.ir Please cite this article as: Behzadi Sheikhrobat S, Kaydani GA, Makvandi M, Rajaee E, Ahmadi Angali K. The Frequency of Human Polyomavirus BK in Patients with Systemic Lupus Erythematosus: A Cross-Sectional Case-Control Study. Arch Med Lab Sci. 2021;7:1-6 (e5). https://doi.org/10.22037/amls.v7.33998